Mast Cells Induce Blood Brain Barrier Damage in SCD by Causing Endoplasmic Reticulum Stress in the Endothelium - Tran, Huy; Mittal, Aditya; Sagi, Varun; Luk, Kathryn; Nguyen, Aithanh; Gupta, Mihir; Nguyen, Julia; Lamarre, Yann; Lei, Jianxun; Guedes, Alonso; Gupta, Kalpna (Frontiers in Cellular Neuroscience, 2019)
Endothelial dysfunction underlies the pathobiology of cerebrovascular disease. Mast cells are located in close proximity to the vasculature, and vasoactive mediators released upon their activation can promote endothelial activation leading to blood brain barrier (BBB) dysfunction. We examined the mechanism of mast cell-induced endothelial activation via endoplasmic reticulum (ER) stress mediated P-selectin expression in a transgenic mouse model of sickle cell disease (SCD), which shows BBB dysfunction. We used mouse brain endothelial cells (mBECs) and mast cells-derived from skin of control and sickle mice to examine the mechanisms involved. Compared to control mouse mast cell conditioned medium (MCCM), mBECs incubated with sickle mouse MCCM showed increased, structural disorganization and swelling of the ER and Golgi, aggregation of ribosomes, ER stress marker proteins, accumulation of galactose-1-phosphate uridyl transferase, mitochondrial dysfunction, reactive oxygen species production, P-selectin expression and mBEC permeability. These effects of sickle-MCCM on mBEC were inhibited by Salubrinal, a reducer of ER stress. Histamine levels in the plasma, skin releasate and in mast cells of sickle mice were higher compared to control mice. Compared to control BBB permeability was increased in sickle mice. Treatment of mice with imatinib, Salubrinal, or P-selectin blocking antibody reduced BBB permeability in sickle mice. Mast cells induce endothelial dysfunction via ER stress-mediated P-selectin expression. Mast cell activation contributes to ER stress mediated endothelial P-selectin expression leading to increased endothelial permeability and impairment of BBB. Targeting mast cells and/or ER stress has the potential to ameliorate endothelial dysfunction in SCD and other pathobiologies.